“Making Positive Vibrations” in a mixed methods study of covert bullying: A transformative methodological framework for social justice - Ingrid E. Hunt-Anderson (Methods in Psychology)
Grounded in critical theory, the exemplar qualitative-oriented exploratory mixed methods study of covert bullying illustrates a methodological framework that adheres to the assumptions of the transformative agenda for prioritizing advocacy and social justice. This includes organizing a multiethnic mix of adolescents from varied school communities and backgrounds and multiple, creative methods to capture rich, “culturally complex” data. Six principles of a transformative framework are charted to help establish cultural legitimacy of the integrative findings and accurate meta-inferences. These principles ultimately provide a robust approach for developing a more authentic picture of covert bullying in Jamaican schools and effective transformative interventions.